Inhibition of the MAPK signaling pathway by red rice extract in UVB-irradiated human skin fibroblasts - Limtrakul P. (2017)
Red rice has demonstrated several biological properties including anti-oxidant and anti-inflammation properties. However, the anti-photoaging activity has not yet been investigated. The aim of this study relates to the photo-protective effects of red rice extract (RRE) on UVB-induced skin aging. RRE was prepared and the active compounds and anti-oxidant activity were determined. The cytotoxicity of fibroblasts and secretions of IL-6 and IL-8 were evaluated. The effects of RRE on collagen and hyaluronic acid (HA) synthesis from fibroblasts were evaluated. Then, the collagenase and MMP-2 activity was determined. The effect of RRE on UV-induced MMP-1, nuclear factor kappa B (NF-κB), activator protein-1 (AP-1) and phosphorylation of MAPK protein expression was determined by western blot analysis. The RRE exerted a free radical scavenging property. RRE significantly increased collagen and HA synthesis in UVB-irradiated human fibroblasts. Moreover, RRE significantly inhibited UVB induced MMP-1 expression, MMP-2 and collagenase activity. Upon UVB irradiation, mitogen activated protein kinases (MAPKs) is activated and this pathway stimulates the expression of interleukin-6 and-8 (IL-6 and-8). Our results show that RRE decreases UVB-induced IL-6 and -8 production and the phosphorylation of c-Jun NH2- terminal kinase (JNK) and the p38 MAPK signaling process. In addition, RRE reduced UVB-induced activation of NF-κB and AP-1. RRE could suppress UV-induced inflammation and skin aging via the inhibition of the MAPK signaling pathway leading to the decrease of NF-κB and AP-1 activation resulting in a decrease in ECM degradation and an increase in ECM synthesis.